Practicing acroyoga in the space of possibilities: Complexity profile as a heuristic device in sport and exercise research - Raisio, H.; Rask, M.; Rantala, T.; Kuorikoski, T. (Journal of Sports Sciences, 2025)
This article explores the application of complexity science in sports and exercise research, introducing Ashby`s law of requisite variety, Boisot`s and McKelvey`s law of requisite complexity, and Bar-Yam`s complexity profile. These frameworks emphasize the role of complexity in system functionality and shed light on the delicate balance between complexity and scale. Utilising acroyoga as a novel research context, an interpretivist study was conducted to delve into the activity`s complexity profile, revealing the intricate interplay between fostering creativity and maintaining essential regulations. Examining acroyoga practitioners` and influencers` perspectives through the complexity profile underscores the sport`s complexity over scale, offering diverse physical, cognitive, affective, and social benefits. However, the limited emphasis on scaling might confine acroyoga to the fringes, hindering widespread acceptance. This study demonstrates the complexity profile as a heuristic tool, challenging assumptions and encouraging innovative perspectives. Acroyoga serves as a compelling case study, highlighting the complexity-scale balance and paving the way for further exploration and sports-related policy formulation.